Exposure of waterfowl to Clostridium botulinum in France - Meloni, Emma; Le Maréchal, Caroline; Millot, Florian; Payne, Ariane; Calenge, Clément; Mazuet, Christelle; Chemaly, Marianne; Rouxel, Sandra; Poezevara, Typhaine; Avouac, Amandine; Plaquin, Betty; Guillemain, Matthieu; et al. (Frontiers in Conservation Science, 2023)
Botulism in wild birds is a widespread and potentially lethal disease raising major conservation issues. Botulism is also of public health concern. Due to the action of botulinum neurotoxins, mostly produced by Clostridium botulinum, botulism can affect wild birds, livestock, and humans. This study is part of a project aimed at improving our understanding of the pathogenesis of botulism in wild avifauna, which is still poorly understood. Indeed, the prevalence and dynamics of C. botulinum in the digestive tract or in bird tissue, whether as intermittent carriage related to environmental contamination or as part of the normal avian microbiota, is still unknown. In this study, we specifically addressed the presence of a healthy carrier status of wild birds, and its role in outbreaks. To answer this question, we monitored the estimated prevalence of C. botulinum in wild birds through samples from banded and swabbed birds as well as from hunted bird organs. Our results do not support the hypothesis of a healthy carriage outside of outbreaks, which raises the question of the bioavailability of the bacterium and toxin in the environment. Finally, the gene encoding botulinum neurotoxin type E was detected in keel muscle from a hunted bird, showing that recommendations on the consumption of wild bird meat are needed following a botulism outbreak.